Composite-form aluminum-doped cobalt carbonate as well as preparation method and application thereof
By controlling the reaction stage and conditions, the uniformity and particle size controllability of aluminum doped cobalt carbonate are achieved, which solves the problems of uneven doping of aluminum and uncontrollable morphology in traditional methods, and promotes its widespread use in industrial applications.
Patent Information
- Application Number
- CN202411854553.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-03-28
AI Technical Summary
In the traditional preparation method of aluminum doped cobalt carbonate, aluminum doping is uneven, its morphology and particle size are uncontrollable, resulting in unstable performance and widespread application obstacles in industrial applications.
A method for preparing cobalt carbonate with composite morphology is adopted to control the two growth stages of the first reaction and the second reaction, and the generation and crystal growth of crystalline aluminum are coordinated to achieve the uniformity of aluminum doping and the controllability of particle size.
The aluminum sheets outside the cobalt carbonate matrix are uniformly dispersed, and the uniformity and morphological controllability of aluminum-doped cobalt carbonate are improved. They are suitable for small-particle-sized products and are conducive to widespread application in industry.
Smart Images

Figure CN119706962A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of high-voltage battery materials, and in particular to a composite aluminum-doped cobalt carbonate and a preparation method and application thereof. Background Art
[0002] At high pressure, lithium cobalt oxide (LCO) releases a large amount of Li + , leading to problems such as unstable surface interface and bulk structure distortion. Studies have shown that the interlayer spacing of Al-doped lithium cobalt oxide materials is enlarged, and Li + The diffusion barrier is reduced, which is beneficial to increase the Li + diffusion coefficient and charge-discharge rate. At the same time, Al doping can also increase the Al-O bond energy (ΔHf 298K (Al-O) = 512 kJ·mol -1 ) is greater than the Co-O bond energy (ΔHf 298K (Co-O) = 368 kJ·mol -1 ), thereby improving the structural stability of lithium cobalt oxide under high voltage.
[0003] The traditional preparation method of aluminum-doped cobalt carbonate mainly adopts wet precipitation to precipitate aluminum ions and cobalt ions simultaneously, and then calcination and thermal decomposition are used to prepare aluminum-doped cobalt carbonate. However, in the synthesis stage of crystalline aluminum (basic aluminum cobalt carbonate), high temperature and high stirring are often used, and the crystalline aluminum grows too fast and is densely distributed, resulting in the problem of "honeycomb" aluminum enrichment, which causes the flake crystalline aluminum to protrude locally and grow in agglomeration, making it difficult to disperse evenly in the cobalt carbonate accumulation particles; however, when aluminum is doped at low temperature, the internal amorphous aluminum carbonate will be precipitated in the form of flakes during the washing process, which not only affects the uniformity of aluminum doping, but also has the risk of uncontrollable product morphology and particle size, thereby affecting the performance of aluminum-doped cobalt carbonate during the application process, which is not conducive to its widespread application in industry. Summary of the invention
[0004] Based on this, it is necessary to provide a composite aluminum-doped cobalt carbonate and its preparation method and application to address the above problems; the preparation method not only achieves uniform dispersion of the outer aluminum flakes and improves the uniformity of aluminum doping in cobalt carbonate, but also makes the morphology and particle size of the aluminum-doped cobalt carbonate controllable, which is conducive to the wide application of aluminum-doped cobalt carbonate in industry.
[0005] A method for preparing composite aluminum-doped cobalt carbonate comprises the following steps:
[0006] preparing a first carbonate solution, a second carbonate solution and an aluminum-doped cobalt salt solution;
[0007] Under stirring conditions, adding the aluminum-doped cobalt salt solution and the first carbonate solution into the second carbonate solution for pre-reaction to obtain a reaction solution containing cobalt carbonate crystal nuclei;
[0008] The aluminum-doped cobalt salt solution and the first carbonate solution are continuously added to the reaction solution to carry out a first reaction and a second reaction in sequence to obtain aluminum-doped cobalt carbonate in a composite form, wherein the second reaction includes a first stage and a second stage, in which the mass ratio of the aluminum-doped cobalt salt solution to the first carbonate solution is 1:1-2:1 in the first stage, and in which the mass ratio of the aluminum-doped cobalt salt solution to the first carbonate solution is 0.10:1-0.25:1 in the second stage.
[0009] In one embodiment, the temperature of the first stage is 30°C-50°C;
[0010] And / or, the pH at the end of the first stage is 6-7.
[0011] In one embodiment, the temperature of the second stage is 30°C-50°C;
[0012] And / or, the pH of the second stage is 7-8.
[0013] In one embodiment, the first reaction satisfies at least one of the following conditions:
[0014] (1) The pH of the first reaction is 7-8;
[0015] (2) Temperature is 30°C-50°C;
[0016] (3) The particle size of the aluminum-doped cobalt carbonate obtained after the first reaction is 3.2 μm-3.5 μm.
[0017] In one embodiment, the pre-reaction satisfies at least one of the following conditions:
[0018] (1) When the pre-reaction is completed, the pH value is 7-9;
[0019] (2) Temperature is 30°C-50°C;
[0020] (3) The cobalt carbonate crystal nucleus particle size is 1.5 μm-2.7 μm.
[0021] In one embodiment, the aluminum-doped cobalt salt solution satisfies at least one of the following conditions:
[0022] (1) The mass ratio of aluminum ion to cobalt ion is 0.011:1-0.014:1;
[0023] (2) Cobalt ion concentration is 80 g / L-145 g / L;
[0024] (3) the aluminum source is at least one selected from aluminum sulfate, aluminum chloride, and aluminum nitrate;
[0025] (4) The cobalt salt is at least one selected from cobalt sulfate, cobalt chloride, and cobalt nitrate.
[0026] In one embodiment, the first carbonate solution and the second carbonate solution satisfy at least one of the following conditions:
[0027] (1) The concentration of carbonate in the first carbonate solution is 180 g / L-240 g / L;
[0028] (2) the concentration of carbonate in the second carbonate solution is 35 g / L-45 g / L;
[0029] (3) The first carbonate solution and the second carbonate solution are independently selected from at least one of ammonium bicarbonate solution, ammonium carbonate solution, sodium bicarbonate solution, and sodium carbonate solution.
[0030] A composite aluminum-doped cobalt carbonate has a core-shell structure, wherein the core is cobalt carbonate containing amorphous aluminum and the shell is cobalt carbonate containing crystalline aluminum.
[0031] In one embodiment, the composite aluminum-doped cobalt carbonate satisfies at least one of the following conditions:
[0032] (1) The particle size of the composite aluminum-doped cobalt carbonate is 4 μm-15 μm;
[0033] (2) The thickness ratio of the inner core to the outer shell is 2:1-3:1;
[0034] (3) The diffraction peak intensity ratio of the inner core to the outer shell on the (101) crystal plane is greater than 1.6.
[0035] Aluminum-doped cobalt tetroxide is prepared by calcining the composite aluminum-doped cobalt carbonate.
[0036] The preparation method of the present invention coordinately regulates the generation and crystal growth of crystalline aluminum by controlling the two growth stages of the first reaction and the second reaction. First, during the first reaction, Al is distributed in amorphous form in a cobalt carbonate matrix; then, in the first stage of the second reaction, the aluminum-doped cobalt salt solution and the first carbonate solution are controlled within a specific mass ratio range to form a cobalt-rich environment, inducing the nucleation of crystalline aluminum and uniformly adsorbing it on the surface of the cobalt carbonate matrix; finally, in the second stage of the second reaction, the aluminum-doped cobalt salt solution and the first carbonate solution are controlled within a specific mass ratio range to form an alkali-rich environment, promoting the growth of cobalt carbonate particles and inhibiting the growth of crystalline Al, thereby achieving uniform dispersion of aluminum flakes outside the cobalt carbonate matrix and improving the uniformity of aluminum doping in cobalt carbonate, and making the morphology and particle size of aluminum-doped cobalt carbonate controllable, and being particularly suitable for small-particle products, and being conducive to the wide application of aluminum-doped cobalt carbonate in industry. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0038] Figure 1 This is a scanning electron microscope image of the growth particles obtained in the second stage step of the second reaction of Example 1;
[0039] Figure 2 This is a scanning electron microscope image of the composite aluminum-doped cobalt carbonate prepared in Example 1;
[0040] Figure 3 XRD patterns of the solid phase materials obtained in the second stage of the first reaction and the second reaction obtained in Example 1, wherein A is the XRD diffraction peak of the solid phase material obtained in the first reaction, and B is the XRD diffraction peak of the solid phase material obtained in the second stage of the second reaction;
[0041] Figure 4 This is a cross-sectional electron probe (EPMA-Al) image of the composite aluminum-doped cobalt carbonate prepared in Example 1;
[0042] Figure 5 This is a scanning electron microscope image of the growth particles obtained in the second stage step of the second reaction of Example 2;
[0043] Figure 6 This is a scanning electron microscope image of the composite aluminum-doped cobalt carbonate prepared in Example 2;
[0044] Figure 7 This is a cross-sectional electron probe (EPMA-Al) image of the composite aluminum-doped cobalt carbonate prepared in Example 2;
[0045] Figure 8 This is a scanning electron microscope image of the growth particles obtained in the second stage step of the second reaction of Comparative Example 1;
[0046] Fig. 9 This is a scanning electron microscope image of the composite aluminum-doped cobalt carbonate prepared in Comparative Example 1;
[0047] Fig.10 This is a scanning electron microscope image of the growth particles obtained in the first stage step of the second reaction of Comparative Example 2;
[0048] Fig.11 This is a scanning electron microscope image of the composite aluminum-doped cobalt carbonate prepared in Comparative Example 2;
[0049] Fig.12 This is the cross-sectional electron probe (EPMA-Al) image of the composite aluminum-doped cobalt carbonate prepared in Comparative Example 2. DETAILED DESCRIPTION
[0050] For ease of understanding of the present invention, the present invention will be described in more detail below. However, it should be understood that the present invention can be implemented in many different forms and is not limited to the embodiments or examples described herein. On the contrary, the purpose of providing these embodiments or examples is to make the understanding of the disclosure of the present invention more thorough and comprehensive.
[0051] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific implementation methods or embodiments, and are not intended to limit the present invention. The optional scope of the term "and / or" used herein includes any one of two or more related listed items, and also includes any and all combinations of related listed items, and the combinations include any two related listed items, any more related listed items, or all related listed items.
[0052] The present application provides a method for preparing aluminum-doped cobalt carbonate in a composite form, comprising the following steps:
[0053] S1, preparing a first carbonate solution, a second carbonate solution and an aluminum-doped cobalt salt solution;
[0054] S2, adding the aluminum-doped cobalt salt solution and the first carbonate solution to a second carbonate solution under stirring conditions for pre-reaction to obtain a reaction solution containing cobalt carbonate crystal nuclei;
[0055] S3, continuously adding the aluminum-doped cobalt salt solution and the first carbonate solution into the reaction solution to carry out a first reaction and a second reaction in sequence to obtain aluminum-doped cobalt carbonate in a composite form, wherein the second reaction includes a first stage and a second stage, in the first stage, the mass ratio of the aluminum-doped cobalt salt solution to the first carbonate solution is 1:1-2:1, and in the second stage, the mass ratio of the aluminum-doped cobalt salt solution to the first carbonate solution is 0.10:1-0.25:1.
[0056] In step S1, preferably, in the aluminum-doped cobalt salt solution, the mass ratio of aluminum ions to cobalt ions is 0.011:1-0.014:1, including but not limited to any point value among 0.011:1, 0.012:1, 0.013:1, 0.014:1 or any range value between two of them.
[0057] In one embodiment, the cobalt ion concentration in the aluminum-doped cobalt salt solution is 80 g / L-145 g / L, including but not limited to any point value among 80 g / L, 90 g / L, 100 g / L, 110 g / L, 120 g / L, 130 g / L, 140 g / L, 145 g / L or a range value between any two of them.
[0058] Specifically, the aluminum source in the aluminum-doped cobalt salt solution is selected from soluble aluminum salts, including but not limited to at least one of aluminum sulfate, aluminum chloride, and aluminum nitrate; the cobalt salt in the aluminum-doped cobalt salt solution is selected from soluble cobalt salts, including but not limited to at least one of cobalt sulfate, cobalt chloride, and cobalt nitrate.
[0059] Preferably, the concentration of carbonate in the first carbonate solution is greater than the concentration of carbonate in the second carbonate solution, which is more conducive to controlling the size uniformity of the cobalt carbonate seed crystals.
[0060] In one embodiment, the concentration of carbonate in the first carbonate solution is preferably 180 g / L-240 g / L, including but not limited to any point value among 180 g / L, 190 g / L, 200 g / L, 210 g / L, 220 g / L, 230 g / L, 240 g / L or a range value between any two of them.
[0061] In one embodiment, the concentration of carbonate in the second carbonate solution is preferably 35 g / L-45 g / L, including but not limited to any point value among 35 g / L, 40 g / L, 45 g / L or any range value between two of them.
[0062] Specifically, the first carbonate solution and the second carbonate solution are independently selected from at least one of ammonium bicarbonate solution, ammonium carbonate solution, sodium bicarbonate solution, and sodium carbonate solution. It is understandable that the first carbonate solution and the second carbonate solution can be selected from the same carbonate solution, for example, the first carbonate solution is diluted and used as the second carbonate solution; the first carbonate solution and the second carbonate solution can also be selected from different carbonate solutions, and the present invention is not limited to this.
[0063] It should be noted that the present invention does not limit the solvents for preparing the first carbonate solution, the second carbonate solution and the aluminum-doped cobalt salt solution, including but not limited to water or organic solvents, preferably pure water.
[0064] In step S2, it is preferred to add the aluminum-doped cobalt salt solution and the first carbonate solution into the second carbonate solution in a cocurrent feeding manner for pre-reaction, which is more conducive to forming cobalt carbonate seed crystals with uniform particle size.
[0065] In one embodiment, the temperature of the pre-reaction is preferably 30°C-50°C, including but not limited to any point value among 30°C, 35°C, 40°C, 45°C, 50°C or any range value therebetween.
[0066] In one embodiment, the pre-reaction is terminated when the pH of the reaction system reaches about 7-9, that is, the pH at the end of the pre-reaction is 7-9. It can be understood that the pH of the pre-reaction is the pH of the solution in the reaction device.
[0067] In one embodiment, the particle size of the cobalt carbonate seed crystals is preferably 1.5 μm-2.7 μm, including but not limited to any point value among 1.5 μm, 1.6 μm, 1.8 μm, 2.0 μm, 2.1 μm, 2.5 μm, 2.7 μm or any range value between two thereof.
[0068] In step S3, by controlling the two growth stages of the first reaction and the second reaction, the generation and crystal growth of crystalline aluminum are coordinated and regulated. First, during the first reaction, Al is distributed in the cobalt carbonate matrix in an amorphous state; then, in the first stage of the second reaction, the aluminum-doped cobalt salt solution and the first carbonate solution are controlled within a specific mass ratio range to form a cobalt-rich environment, inducing the nucleation of crystalline aluminum and uniformly adsorbing it on the surface of the cobalt carbonate matrix; finally, in the second stage of the second reaction, the aluminum-doped cobalt salt solution and the first carbonate solution are controlled within a specific mass ratio range to form an alkali-rich environment, promoting the growth of cobalt carbonate particles and inhibiting the growth of crystalline Al, so that nano-scale basic aluminum cobalt carbonate is embedded in the cobalt carbonate matrix, thereby effectively avoiding the formation of "honeycomb aluminum", making the aluminum flakes outside the cobalt carbonate matrix evenly dispersed, improving the uniformity of aluminum doping in cobalt carbonate, and effectively controlling the morphology and particle size of aluminum-doped cobalt carbonate.
[0069] In one embodiment, the mass ratio of the aluminum-doped cobalt salt solution to the first carbonate solution in the first stage includes but is not limited to any point value among 1:1, 1.1:1, 1.2:1, 1.5:1, 1.6:1, 1.8:1, 2:1 or a range value between any two of them, preferably 1.6:1-2:1.
[0070] More preferably, the temperature of the first stage is 30°C-50°C; when the pH of the reaction system reaches about 6-7, the first stage reaction is terminated, that is, the pH is 6-7 when the first stage ends.
[0071] In one embodiment, the mass ratio of the aluminum-doped cobalt salt solution to the first carbonate solution in the second stage includes but is not limited to any point value among 0.10:1, 0.12:1, 0.15:1, 0.18:1, 0.20:1, 0.23:1, 0.25:1 or a range value between any two of them, preferably 0.10:1-0.15:1.
[0072] More preferably, the temperature of the second stage is 30°C-50°C; the pH of the second stage is preferably 7-8.
[0073] In one embodiment, the temperature of the first reaction is preferably 30°C-50°C.
[0074] In one embodiment, the pH of the first reaction is preferably 7-8.
[0075] It should be noted that the pH and temperature of the two growth stages of the pre-reaction, the first reaction and the second reaction may be the same or different, and the present invention does not impose any limitation on this.
[0076] In one embodiment, the particle size of the aluminum-doped cobalt carbonate obtained after the first reaction is preferably 3.2 μm-3.5 μm, including but not limited to any point value among 3.2 μm, 3.3 μm, 3.4 μm, 3.5 μm or any range value between two of them.
[0077] In one embodiment, after the second reaction is completed, the particles are preferably washed with water at 50° C. to 80° C. for 20 min to 50 min, and then dried to obtain composite aluminum-doped cobalt carbonate particles, wherein the drying method is preferably flash drying.
[0078] Therefore, the preparation method of the present invention adopts the means of promoting the formation of crystalline aluminum nuclei by positive reaction and inhibiting the growth by supersaturation, which not only realizes the uniform dispersion of aluminum flakes outside the cobalt carbonate matrix and improves the uniformity of aluminum doping in cobalt carbonate, but also makes the morphology and particle size of aluminum-doped cobalt carbonate controllable, is particularly suitable for small-particle products, and is conducive to the wide application of aluminum-doped cobalt carbonate in industry.
[0079] The present invention provides a composite aluminum-doped cobalt carbonate, wherein the composite aluminum-doped cobalt carbonate has a core-shell structure, wherein the core is cobalt carbonate containing amorphous aluminum, and the shell is cobalt carbonate containing crystalline aluminum. It should be noted that the core includes a crystal core and a first layer structure formed on the surface of the crystal core by a first reaction, and the shell includes a second layer structure formed in the first stage of the second reaction and a third layer structure formed in the second stage. It is understandable that there is no obvious boundary between the crystal core, the first layer structure, the second layer structure and the third layer structure. The composite aluminum-doped cobalt carbonate is preferably prepared by the preparation method as described above.
[0080] The composite aluminum-doped cobalt carbonate provided by the present invention overcomes the problems of outer aluminum enrichment, uneven aluminum doping, uncontrollable product morphology and particle size in traditional aluminum-doped cobalt carbonate, and achieves better inheritance of aluminum doping uniformity in cobalt oxide particles and lithium cobaltate materials.
[0081] In one embodiment, the particle size of the composite aluminum-doped cobalt carbonate is 4μm-15μm, preferably 4μm-6μm, including but not limited to any point value among 4μm, 4.5μm, 5μm, 5.5μm, 6μm, 8μm, 10μm, 12μm, 15μm or any range value between two thereof.
[0082] In one embodiment, the thickness ratio of the inner core to the outer shell is preferably 2:1-3:1, including but not limited to any value among 2:1, 2.5:1, 3:1 or any range between the two.
[0083] Due to changes in the occurrence form and crystal strength of aluminum, in one embodiment, the diffraction peak intensity of the inner core at the (101) crystal plane is greater than the diffraction peak intensity of the outer shell at the (101) crystal plane. Preferably, the ratio of the diffraction peak intensities of the inner core to the outer shell at the (101) crystal plane is greater than 1.6.
[0084] The present invention also provides an aluminum-doped cobalt oxide, which is prepared by calcining the composite aluminum-doped cobalt carbonate as described above. It is understood that the present invention does not limit the specific conditions for preparing the aluminum-doped cobalt oxide by calcining the composite aluminum-doped cobalt carbonate as described above, and the existing conventional preparation conditions can be used.
[0085] Furthermore, the aluminum-doped cobalt oxide is mixed with a lithium source and sintered to obtain a lithium cobalt oxide positive electrode material, which can be used in lithium-ion batteries.
[0086] Hereinafter, the composite aluminum-doped cobalt carbonate and its preparation method and application will be further described by the following specific examples. However, those skilled in the art will understand that the following examples are only used to illustrate the present invention and should not be regarded as limiting the scope of the present invention. If no specific conditions are specified in the examples, they are carried out according to conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used without indicating the manufacturer are all conventional products that can be obtained commercially.
[0087] Example 1
[0088] Cobalt sulfate and aluminum sulfate are mixed in proportion to prepare a mixed metal sulfate solution with a metal cobalt ion concentration of 130 g / L and a mass ratio of aluminum ions to cobalt ions of 0.013:1; ammonium bicarbonate is mixed with pure water to prepare an ammonium bicarbonate solution with a concentration of 220 g / L.
[0089] Ammonium bicarbonate and pure water were added into a reaction kettle as a base liquid, the concentration of ammonium bicarbonate in the base liquid was 40 g / L, stirring was started and the temperature was raised to 45° C. A mixed metal sulfate solution and an ammonium bicarbonate solution were added into the reaction kettle in a parallel flow manner to cause a precipitation reaction, the reaction pH was controlled to be about 7.7, and a seed crystal with a particle size of 1.7 μm was prepared.
[0090] The mixed metal sulfate solution and ammonium bicarbonate solution prepared above were continuously added to the reaction solution containing cobalt carbonate seeds, the reaction temperature was set to 45°C, the reaction pH was controlled to be about 7.5, and continuous feeding was performed through the built-in concentrator to grow the primary growth particles to 3.5 μm.
[0091] Continue to add the prepared mixed metal sulfate solution and ammonium bicarbonate solution into the built-in concentrating kettle, set the reaction temperature to 45°C, adjust the feed pump flow rate so that the mass ratio of the mixed metal sulfate solution to the ammonium bicarbonate solution is 2:1, and when the system pH reaches about 6.5, adjust the ammonium bicarbonate solution feed pump flow rate so that the mass ratio of the mixed metal sulfate solution to the ammonium bicarbonate solution is 0.15:1, and control the system pH to about 7.5, and feed the feed until the aluminum-doped cobalt carbonate grows to 4.0 μm, and continue to maintain until the aluminum-doped cobalt carbonate grows to 5.0 μm, and terminate the reaction.
[0092] The slurry containing aluminum-doped cobalt carbonate is passed into a centrifuge, washed with 70° C. water for 30 minutes, centrifugally dehydrated, and then dried by a flash evaporator to obtain aluminum-doped cobalt carbonate in a composite form.
[0093] The second stage of the second reaction and the scanning electron microscope (SEM) images of the obtained composite aluminum-doped cobalt carbonate are shown in FIG. Figure 1 and Figure 2 As shown in Figure 2, electron microscopy shows that the outer aluminum layer is evenly distributed. The XRD patterns of the solid phase materials in the first and second reactions are shown in Figure 2. Figure 3 As shown, the ratio of the diffraction peak intensity of the first reaction solid material (101) crystal surface to the diffraction peak intensity of the second reaction second stage solid phase material (101) crystal surface is greater than 1.6. The cross section of the composite aluminum-doped cobalt carbonate was subjected to electron probe analysis, and the results are as follows: Figure 4 As shown, the highest signal value of aluminum is 61, and there is no color difference inside and outside, proving that the aluminum is evenly distributed inside and outside.
[0094] Example 2
[0095] Cobalt sulfate and aluminum sulfate are mixed in proportion to prepare a mixed metal sulfate solution with a metal cobalt ion concentration of 140 g / L and a mass ratio of aluminum ions to cobalt ions of 0.011:1; ammonium bicarbonate is mixed with pure water to prepare an ammonium bicarbonate solution with a concentration of 240 g / L.
[0096] Ammonium bicarbonate and pure water were added into a reaction kettle as a base liquid, the concentration of ammonium bicarbonate in the base liquid was 35 g / L, stirring was started and the temperature was raised to 48° C. A mixed metal sulfate solution and an ammonium bicarbonate solution were added into the reaction kettle in a parallel flow manner to cause a precipitation reaction, the reaction pH was controlled to be about 7.8, and a seed crystal with a particle size of 1.5 μm was prepared.
[0097] The mixed metal sulfate solution and ammonium bicarbonate solution prepared above were continuously added to the reaction solution containing cobalt carbonate seeds, the reaction temperature was set to 48°C, the reaction pH was controlled to be about 7.6, and continuous feeding was performed through the built-in concentrator to grow the primary growth particles to 3.2 μm.
[0098] Continue to add the prepared mixed metal sulfate solution and ammonium bicarbonate solution into the built-in concentrating kettle, set the reaction temperature to 48°C, adjust the feed pump flow rate so that the mass ratio of the mixed metal sulfate solution to the ammonium bicarbonate solution is 1.8:1, and when the system pH reaches about 6.6, adjust the feed pump flow rate of the ammonium bicarbonate solution so that the mass ratio of the mixed metal sulfate solution to the ammonium bicarbonate solution is 0.20:1, and control the system pH to about 7.4, and feed the feed until the aluminum-doped cobalt carbonate grows to 4.4 μm, and continue to maintain until the aluminum-doped cobalt carbonate grows to 5.5 μm, and terminate the reaction.
[0099] The slurry containing aluminum-doped cobalt carbonate was passed into a centrifuge, washed with 70° C. water for 35 minutes, centrifuged and dehydrated, and then dried by a flash evaporator to obtain aluminum-doped cobalt carbonate in a composite form.
[0100] The second stage of the second reaction and the scanning electron microscope (SEM) images of the obtained composite aluminum-doped cobalt carbonate are shown in FIG. Figure 5 and Figure 6 As shown in Figure 1, electron microscopy shows that the outer layer of aluminum is evenly distributed. Electron probe analysis of the cross section of the composite aluminum-doped cobalt carbonate is performed, and the results are shown in Figure 1. Figure 7 As shown, the highest signal value of aluminum is 51, and there is no color difference inside and outside, proving that the aluminum is evenly distributed inside and outside.
[0101] Example 3
[0102] The difference between Example 3 and Example 1 is that after the primary growth particles grow to 3.5 μm, the mixed metal sulfate solution and ammonium bicarbonate solution prepared above are continuously added to the built-in concentrating kettle, the reaction temperature is set to 45°C, and the feed pump flow rate is adjusted so that the mass ratio of the mixed metal sulfate solution to the ammonium bicarbonate solution is 1.6:1. When the system pH reaches about 6.4, the feed pump flow rate of the ammonium bicarbonate solution is adjusted so that the mass ratio of the mixed metal sulfate solution to the ammonium bicarbonate solution is 0.10:1, and the system pH is controlled to be about 7.3, and the feed is added in parallel until the aluminum-doped cobalt carbonate grows to 4.2 μm, and the reaction is terminated until the aluminum-doped cobalt carbonate grows to 4.8 μm.
[0103] The slurry containing aluminum-doped cobalt carbonate is passed into a centrifuge, washed with 60° C. water for 30 minutes, centrifugally dehydrated, and then dried by a flash evaporator to obtain aluminum-doped cobalt carbonate in a composite form.
[0104] Electron probe analysis of the cross section of the composite aluminum-doped cobalt carbonate showed no color difference inside and outside, proving that the aluminum is evenly distributed inside and outside.
[0105] Example 4
[0106] The difference between Example 4 and Example 1 is that after the primary growth particles grow to 3.5 μm, the above-prepared mixed metal sulfate solution and ammonium bicarbonate solution are continuously added to the built-in concentrating kettle, the reaction temperature is set to 45°C, and the feed pump flow rate is adjusted so that the mass ratio of the mixed metal sulfate solution to the ammonium bicarbonate solution is 1:1. When the system pH reaches about 6.7, the feed pump flow rate of the ammonium bicarbonate solution is adjusted so that the mass ratio of the mixed metal sulfate solution to the ammonium bicarbonate solution is 0.25:1, and the system pH is controlled to be about 7.6, and the feed is added in parallel until the aluminum-doped cobalt carbonate grows to 5.2 μm, and the reaction is terminated by continuing to maintain the growth of the aluminum-doped cobalt carbonate to 6 μm.
[0107] The slurry containing aluminum-doped cobalt carbonate is passed into a centrifuge, washed with 60° C. water for 30 minutes, centrifugally dehydrated, and then dried by a flash evaporator to obtain aluminum-doped cobalt carbonate in a composite form.
[0108] Electron probe analysis of the cross section of the composite aluminum-doped cobalt carbonate showed no color difference inside and outside, proving that the aluminum is evenly distributed inside and outside.
[0109] Comparative Example 1
[0110] Cobalt sulfate and aluminum sulfate are mixed in proportion to prepare a mixed metal sulfate solution with a metal cobalt ion concentration of 120 g / L and a mass ratio of aluminum ions to cobalt ions of 0.011:1; ammonium bicarbonate is mixed with pure water to prepare an ammonium bicarbonate solution with a concentration of 220 g / L.
[0111] Add ammonium bicarbonate and pure water as the base liquid into the reactor, wherein the concentration of ammonium bicarbonate in the base liquid is 38 g / L, start stirring and raise the temperature to 35° C. Add the above-prepared mixed metal sulfate solution and ammonium bicarbonate solution into the reactor in a parallel flow manner to cause precipitation reaction, control the reaction pH to be about 7.5, and prepare seed crystals with a particle size of 1.9 μm.
[0112] The mixed metal sulfate solution and ammonium bicarbonate solution prepared above were continuously added to the reaction solution containing cobalt carbonate seeds, the reaction temperature was set at 30°C, the reaction pH was controlled to be about 7.6, and continuous feeding was performed through the built-in concentrator to grow the primary growth particles to 3.0 μm.
[0113] Continue to add the above-prepared mixed metal sulfate solution and ammonium bicarbonate solution into the built-in concentrating kettle, set the reaction temperature to 30°C, adjust the flow rate of the feeding pump to make the mass ratio of the mixed metal sulfate solution to the ammonium bicarbonate solution 0.15:1, and control the system pH to be about 7.8, and feed in parallel until the aluminum-doped cobalt carbonate grows to 4.2μm, and terminate the reaction.
[0114] The slurry containing aluminum-doped cobalt carbonate was passed into a centrifuge, washed with 70° C. water for 35 minutes, centrifuged and dehydrated, and then dried by a flash evaporator to obtain aluminum-doped cobalt carbonate.
[0115] The second stage of the second reaction and the scanning electron microscope (SEM) images of the obtained aluminum-doped cobalt carbonate are shown in FIG. Figure 8 and Fig. 9 As shown, due to the lack of a cobalt-rich environment in the second reaction, the crystal transformation could not be induced successfully. Therefore, after centrifugal washing, the amorphous aluminum carbonate water inside the particles was precipitated, seriously affecting the uniformity of aluminum doping.
[0116] Comparative Example 2
[0117] Cobalt sulfate and aluminum sulfate are mixed in proportion to prepare a mixed metal sulfate solution with a metal cobalt ion concentration of 110 g / L and a mass ratio of aluminum ions to cobalt ions of 0.013:1; ammonium bicarbonate is mixed with pure water to prepare an ammonium bicarbonate solution with a concentration of 220 g / L.
[0118] Add ammonium bicarbonate and pure water as the base liquid into the reactor, wherein the concentration of ammonium bicarbonate in the base liquid is 40 g / L, start stirring and raise the temperature to 35° C. Add the above-prepared mixed metal sulfate solution and ammonium bicarbonate solution into the reactor in a parallel flow manner to cause precipitation reaction, control the reaction pH to be about 7.5, and prepare seed crystals with a particle size of 1.8 μm.
[0119] The mixed metal sulfate solution and ammonium bicarbonate solution prepared above were continuously added to the reaction solution containing cobalt carbonate seeds, the reaction temperature was set to 30°C, the reaction pH was controlled to be about 7.5, and continuous feeding was performed through the built-in concentrator to grow the primary growth particles to 3.0 μm.
[0120] Continue to add the above-prepared mixed metal sulfate solution and ammonium bicarbonate solution into the built-in concentrating kettle, set the reaction temperature to 30°C, adjust the flow rate of the feeding pump so that the mass ratio of the mixed metal sulfate solution to the ammonium bicarbonate solution is 1.5:1, and control the system pH to be about 7.0, and feed the feed until the aluminum-doped cobalt carbonate grows to 4.5μm, and terminate the reaction.
[0121] The slurry containing aluminum-doped cobalt carbonate was passed into a centrifuge, washed with 70° C. water for 35 minutes, centrifuged and dehydrated, and then dried by a flash evaporator to obtain aluminum-doped cobalt carbonate.
[0122] The first stage of the second reaction and the scanning electron microscope (SEM) images of the aluminum-doped cobalt carbonate obtained are shown in FIG. Fig.10 and Fig.11 As shown in the figure, in the second reaction, although there is a cobalt-rich environment to induce the transformation of the crystal form, the lack of an alkali-rich environment will lead to the intensification of the decomposition of ammonium carbonate, and OH - 、CO3 2- The release rate is fast, resulting in the protruding growth of crystalline aluminum sheets; as the reaction proceeds, the outer layer shows "honeycomb aluminum" enrichment, which seriously affects the uniformity of aluminum doping in the outer layer. Electron probe analysis of the cross section of aluminum-doped cobalt carbonate is performed, and the results are as follows Fig.12 As shown, there is a clear color difference between the inside and outside, and the aluminum distribution of the inner and outer layers is uneven.
[0123] Comparative Example 3
[0124] The difference between Comparative Example 3 and Example 1 is that the mass ratio of the mixed metal sulfate solution to the ammonium bicarbonate solution in the first stage is regulated to be 1:2.
[0125] Comparative Example 4
[0126] The difference between Comparative Example 4 and Example 1 is that the mass ratio of the mixed metal sulfate solution to the ammonium bicarbonate solution in the first stage is regulated to be 3:1.
[0127] Comparative Example 5
[0128] The difference between Comparative Example 5 and Example 1 is that the mass ratio of the mixed metal sulfate solution to the ammonium bicarbonate solution in the second stage is regulated to be 0.05:1.
[0129] Comparative Example 6
[0130] The difference between Comparative Example 6 and Example 1 is that the mass ratio of the mixed metal sulfate solution to the ammonium bicarbonate solution in the second stage is regulated to be 0.3:1.
[0131] The aluminum-doped cobalt carbonate obtained in Examples 3-6 was subjected to electron probe analysis. The results showed that the mass ratio range between the cobalt-rich environment and the alkali-rich environment is particularly important. Deviating from this range will lead to the problem of being unable to induce crystalline aluminum transformation or crystalline aluminum enrichment growth, seriously affecting the uniformity of aluminum doping in the outer layer.
[0132] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0133] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing aluminum-doped cobalt carbonate in a composite form, characterized in that: The steps include: preparing a first carbonate solution, a second carbonate solution and an aluminum-doped cobalt salt solution; Under stirring conditions, adding the aluminum-doped cobalt salt solution and the first carbonate solution into the second carbonate solution for pre-reaction to obtain a reaction solution containing cobalt carbonate crystal nuclei; The aluminum-doped cobalt salt solution and the first carbonate solution are continuously added to the reaction solution to carry out a first reaction and a second reaction in sequence to obtain aluminum-doped cobalt carbonate in a composite form, wherein the second reaction includes a first stage and a second stage, in which the mass ratio of the aluminum-doped cobalt salt solution to the first carbonate solution is 1:1-2:1 in the first stage, and in which the mass ratio of the aluminum-doped cobalt salt solution to the first carbonate solution is 0.10:1-0.25:1 in the second stage.
2. The method for preparing composite aluminum-doped cobalt carbonate according to claim 1, characterized in that: The temperature of the first stage is 30°C-50°C; And / or, the pH at the end of the first stage is 6-7.
3. The method for preparing composite aluminum-doped cobalt carbonate according to claim 1, characterized in that: The temperature of the second stage is 30°C-50°C; And / or, the pH of the second stage is 7-8.
4. The method for preparing composite aluminum-doped cobalt carbonate according to claim 1, characterized in that: The first reaction satisfies at least one of the following conditions: (1) The pH of the first reaction is 7-8; (2) Temperature is 30°C-50°C; (3) The particle size of the aluminum-doped cobalt carbonate obtained after the first reaction is 3.2 μm-3.5 μm.
5. The method for preparing composite aluminum-doped cobalt carbonate according to claim 1, characterized in that: The pre-reaction satisfies at least one of the following conditions: (1) When the pre-reaction is completed, the pH value is 7-9; (2) Temperature is 30°C-50°C; (3) The cobalt carbonate crystal nucleus particle size is 1.5 μm-2.7 μm.
6. The method for preparing composite aluminum-doped cobalt carbonate according to claim 1, characterized in that: The aluminum-doped cobalt salt solution satisfies at least one of the following conditions: (1) The mass ratio of aluminum ion to cobalt ion is 0.011:1-0.014:1; (2) Cobalt ion concentration is 80 g / L-145 g / L; (3) the aluminum source is at least one selected from aluminum sulfate, aluminum chloride, and aluminum nitrate; (4) The cobalt salt is at least one selected from cobalt sulfate, cobalt chloride, and cobalt nitrate.
7. The method for preparing composite aluminum-doped cobalt carbonate according to claim 1, characterized in that: The first carbonate solution and the second carbonate solution satisfy at least one of the following conditions: (1) The concentration of carbonate in the first carbonate solution is 180 g / L-240 g / L; (2) the concentration of carbonate in the second carbonate solution is 35 g / L-45 g / L; (3) The first carbonate solution and the second carbonate solution are independently selected from at least one of ammonium bicarbonate solution, ammonium carbonate solution, sodium bicarbonate solution, and sodium carbonate solution.
8. A composite aluminum-doped cobalt carbonate, characterized in that: The composite aluminum-doped cobalt carbonate has a core-shell structure, wherein the core is cobalt carbonate containing amorphous aluminum and the shell is cobalt carbonate containing crystalline aluminum.
9. The composite aluminum-doped cobalt carbonate according to claim 8, characterized in that: The composite aluminum-doped cobalt carbonate satisfies at least one of the following conditions: (1) The particle size of the composite aluminum-doped cobalt carbonate is 4 μm-15 μm; (2) The thickness ratio of the inner core to the outer shell is 2:1-3:1; (3) The diffraction peak intensity ratio of the inner core to the outer shell on the (101) crystal plane is greater than 1.
6.
10. An aluminum-doped cobalt oxide, characterized in that: It is obtained by calcining the composite aluminum-doped cobalt carbonate as described in claim 8 or 9.
Citation Information
Cited By
High-aluminum doped cobalt carbonate as well as preparation method and application thereof
CN120535022A